SP36 Opioid sparing anesthesia. (11th August 2022) - Lirk, P
Abstract : University of Nebraska Medical Center, USA Inadequate perioperative pain control delays postoperative mobilization, and may lead to development of chronic postoperative pain, amplified cardiac and pulmonary complications, and increased morbidity and mortality. 1 Even though opioids are still widely used, 2 more information on their misuse, limitations and side-effects is becoming available, including risk of dependence and opioid-induced hyperalgesia (OIH). 3 Multimodal analgesia has been defined as the use of two or more analgesics or techniques that target different mechanisms or pathways in the nociceptive system. 4 As drugs are combined, lower doses of each class can be given, thereby lowering the side effects of each individual drug, but increasing overall efficacy. 5, 6 Drugs commonly used in this framework include acetaminophen, non-steroidal anti-inflammatory drugs (NSAID) or cyclo-oxygenase-2 inhibitors, dexamethasone, gabapentin, clonidine, dexmedetomidine, intravenous lidocaine, magnesium and ketamine. When timed correctly, however, regional anesthesia remains the best and most powerful opioid-sparing technique for many indications. References: Gerbershagen HJ, Aduckathil S, van Wijck AJ, et al . Pain intensity on the first day after surgery: a prospective cohort study comparing 179 surgical procedures. Anesthesiology 2013;118:934–44. Ladha KS, Patorno E, Huybrechts KF, et al . Variations in the Use of Perioperative Multimodal Analgesic Therapy. Anesthesiology 2016;124:837–45. Wu CL, Raja SN. Treatment of acute postoperative pain. Lancet 2011;377:2215–25. Manworren RC. Multimodal pain management and the future of a personalized medicine approach to pain. AORN J 2015;101:308–14; quiz 15–8. Kehlet H, Dahl JB. The value of 'multimodal' or 'balanced analgesia' in postoperative pain treatment. Anesth Analg 1993;77:1048–56. Buvanendran A, Kroin JS. Multimodal analgesia for controlling acute postoperative pain. Curr Opin Anaesthesiol 2009;22:588–93.